AMXT-1501 targets membrane phospholipids against Gram-positive and -negative multidrug-resistant bacteria - Jinxin Zheng; Xiaoju Liu; Yanpeng Xiong; Qingyin Meng; Peiyu Li; Fan Zhang; Xiaoming Liu; Zhiwei Lin; Qiwen Deng; Zewen Wen; Zhijian Yu (Emerging Microbes and Infections)
The rapid proliferation of multidrug-resistant (MDR) bacterial pathogens poses a serious threat to healthcare worldwide. Carbapenem-resistant (CR) Enterobacteriaceae, which have near-universal resistance to available antimicrobials, represent a particularly concerning issue. Herein, we report the identification of AMXT-1501, a polyamine transport system inhibitor with antibacterial activity against Gram-positive and -negative MDR bacteria. We observed minimum inhibitory concentration (MIC)50/MIC90 values for AMXT-1501 in the range of 3.13–12.5 μM (2.24–8.93 μg /mL), including for methicillin-resistant Staphylococcus aureus (MRSA), CR Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. AMXT-1501 was more effective against MRSA and CR E. coli than vancomycin and tigecycline, respectively. Subinhibitory concentrations of AMXT-1501 reduced the biofilm formation of S. aureus and Enterococcus faecalis. Mechanistically, AMXT-1501 exposure damaged microbial membranes and increased membrane permeability and membrane potential by binding to cardiolipin (CL) and phosphatidylglycerol (PG). Importantly, AMXT-1501 pressure did not induce resistance readily in the tested pathogens.